Consumer directed care in residential aged care: an evaluation of a staff training program. (2nd April 2020) - McCabe, Marita P.; Beattie, Elizabeth; Karantzas, Gery; Mellor, David; Sanders, Kerrie; Busija, Lucy; Goodenough, Belinda; Bennett, Michelle; von Treuer, Kathryn; Byers, Jessica
Abstract: Objectives: The advent of Consumer-Directed Care (CDC, or individualized care) in Residential Aged Care Facilities (RACFs, or residential care) will require a paradigm shift in service delivery. This article evaluated the six-session Resident at the Centre of Care (RCC) staff training program designed to equip staff to implement a CDC model of care among residents. Method: There were two experimental conditions: RCC training program alone, RCC training program plus support, and a 'care as usual' condition. Outcome measures were resident quality of life (QoL) and resident working relationships with staff at 3-month follow-up. At Time 1, 92 residents from RACFs participated in the program. The RCC is six sessions that focus on the development of staff skills in communicating with residents, as well as the organizational change and transformational leadership that is needed for the implementation of CDC. Results: There were significant improvements in resident QoL. There was no major difference between the RCC Program plus support condition compared to the RCC Program alone condition, but both were associated with more positive changes in resident QoL than the 'care as usual' condition. Conclusion: This study demonstrates that training staff in strategies to implement CDC in RACFs can lead to an improvement in the wellbeing of many residents, and that additional support to assist staff to implement the strategies may not be required to produce such improvements. Longer term follow-up is necessary to determine if the improvements in resident QoL are sustained.